Analisis kepatuhan pajak UMKM di masa pandemi Covid-19: Dampak pengetahuan, sanksi, sosialisasi, dan penerapan e-filling - Paulus, Hendro; Tarmidi, Deden (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2023)
This study aims to analyze the level of taxpayer compliance during the COVID-19 Pandemic, the impact of tax knowledge, tax sanctions, tax socialization and implementation of e-filling. 100 MSMEs in Situsari Village, Bogor Regency, West Java Province, were used as the unit of analysis for this study because they were suspected of having an impact on the existing COVID19 pandemic, coupled with tax incentive regulations from the Government. Using path analysis with the Smart PLS application, this study found that the variables of tax socialization and the implementation of e-Filling had an effect on taxpayer compliance, while the variables of tax knowledge and tax sanctions had no effect. These results contribute to the tax policy taken by the Government, whereby the result is that tax socialization which can affect tax compliance can encourage the Government as the regulator to carry out more tax socialization in various ways and media so that Taxpayers receive tax information as a whole. Likewise, with the discovery of the effect of implementing e-Filling on tax compliance, online tax services can be improved again so that taxpayers can enjoy the benefits of the convenience and usability of these online tax services, as explained in the Technology Acceptance Model.